Sergeant Reckless the true story of the little horse who became a hero - McCormick, Patricia 1956-; Bruno, Iacopo (New York, NY Balzer + Bray, an imprint of HarperCollinsPublishers, 2017)
When a group of US Marines fighting in the Korean War found a bedraggled little mare, they wondered if she could be trained to as a packhorse. They had no idea that the skinny, underfed horse had one of the biggest and bravest hearts they'd ever known. And one of the biggest appetites! Soon Reckless showed herself more than willing to carry ammunition too heavy for the soldiers to haul. As cannons thundered and shells flew through the air, she marched into battle -- again and again -- becoming the only animal ever to officially hold military rank and receive two Purple Hearts.
Includes bibliographical references.
Ages 6-10.
Keywords: Sergeant Reckless -- (Horse) -- approximately 1948-1968 -- Juvenile literature; Sergeant Reckless -- (Horse) -- approximately 1948-1968.; Sergeant Reckless -- (Horse) -- approximately 1948-1968.; 1950-1953; Horses -- Korea -- Biography -- Juvenile literature; War horses -- Juvenile literature; Animals -- War use -- Juvenile literature; Korean War, 1950-1953 -- Juvenile literature; Horses; Animals; Horses -- Korea -- Biography -- Juvenile literature; Horses; Animals -- War use; War horses; Animals -- War use; Horses; Korea; Biographies; Biographies; Biography; Juvenile works; Picture books; Picture books; Biographies